Characterisation of the Trypanosoma brucei rhodesiense isolates from Tanzania using serum resistance associated gene as molecular marker - Kibona, S N; Picozzi, K; Matemba, L; Lubega, G W (Tanzania Journal of Health Research, 2007)
Serum resistance associated (SRA) gene has been found to confer resistance to the innate trypanolytic factor(TLF) found in normal human serum; thus allowing Trypanosoma brucei brucei to survive exposure to normal humanserum. This study was carried out to examine the presence of SRA gene and identify the origin of T. b. rhodesiense isolatesfrom three districts in Tanzania, namely Kibondo, Kasulu and Urambo. Twenty-six T. b. rhodesiense isolates and tworeferences T. b. rhodesiense isolates from Kenya were examined for SRA gene using simple Polymerase Chain Reactiontechnique. The gene was found to be present in all 26 T. b. rhodesiense isolates including the two references isolates fromKenya. The SRA gene was confirmed to be specific to T. b. rhodesiense since it could not be amplified from all otherTrypanozoon including T. b. gambiense; and gave an amplified fragment of the expected size (3.9kb), confirming that allthese isolates were T. b. rhodesiense of the northern variant. Although the geographic distributions of T. b. gambiense andT. b. rhodesiense are clearly localized to west/central Africa and eastern Africa, respectively, natural movement of peopleand recent influx of large number of refugees into Tanzania from the Democratic Republic of Congo, could have broughtT. b. gambiense in western Tanzania. The overlap in distribution of both of these pathogenic sub-species could result inerroneous diagnoses since both trypanosome sub-species are morphologically identical, and currently serologic methodshave low specificity. Both the susceptible and resistant T.b. rhodesiense isolates possessed the SRA gene suggesting thatthere is no correlation between drug resistance and presence of SRA gene. The use of SRA gene helps to confirm theidentity and diversity of some of the isolates resistant to various drugs. Keywords: Trypanosoma brucei rhodesiense, resistance, SRA gene, PCR, Tanzania Tanzania Health Research Bulletin Vol. 9 (1) 2007: pp.25-31